Optimization of banana midrib horn hydrolysis with cobalt-activated zeolite catalyst assisted by ultrasonic for renewable energy - Sri Rahmawati; Sri Wahyuni; M. Rusdi (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
This study aims to convert banana midrib into glucose using a Co-ZAA catalyst with ultrasonic assistance. Characterization was conducted through XRD and XRF analyses to determine the crystallinity, structure, and material composition. XRD results showed that the diffractogram patterns of ZAA and Co-ZAA correspond to the characteristics of mordenite zeolite based on JCPDS references. This similarity is indicated by the appearance of main peaks at 2θ, suggesting high crystallinity and optimal structural order for catalytic activity. XRF analysis revealed that Co-ZAA 15% contains silicon (55.2%) and aluminum (13%), with a Si/Al ratio that supports the material's thermal stability and acidity. The cobalt content of 18.9% confirms successful impregnation, making it an active center in catalytic reactions. Other elements, such as iron (6.16%), calcium (2.93%), and potassium (2.59%), originate from natural zeolite or synthesis residues. A qualitative test using Fehling’s reagent confirmed the presence of reducing sugars in the hydrolysis products, indicated by a color change from blue to yellow and the formation of Cu₂O precipitate. These results demonstrate that the Co-ZAA catalyst is effective in hydrolyzing cellulose into simple sugar compounds, with potential applications in biomass-based industries and renewable energy.